Analysis of the Impact of Underwriting Rates on Return on Assets in Insurance Companies Operating in Syria - الحسامي مجد; يمن أحمد منصور; أحمد أديب أحمد (Latakia University Journal - Economic and Legal Sciences Series, 2024)
The aim of the research was to measure the impact of underwriting rates on the return on assets (ROA) in insurance companies operating in Syria using panel data models. The study covered the period from 2010 to 2021, relying on data issued by the Insurance Supervisory Authority and the Damascus Securities Exchange, including financial data, balance sheets, and income statements of companies present in Syria. The main findings of the research indicate a weak correlation between the variables, suggesting that the study variables are independent of each other. Additionally, there is a positive relationship between the return on assets and the growth rate of underwriting premiums, and a negative relationship between the return on assets and the market share rate. However, the retention rate did not show any statistical significance in the return on assets. The fixed effects model was found to be the most appropriate among the proposed panel data models, with both the market share rate and the growth rate of underwriting premiums being key components of the fixed effects model.